197 Gold Nanoparticle Enhanced X-ray Nanotomography Reveals Region-Specific CSF Pathways Through the Brain and Spinal Cord that are Altered in Post-hemorrhagic Hydrocephalus. (1st April 2022) - Pan, Shelei; DeFreitas, Dakota; Ramagiri, Sruthi; Bayguinov, Peter; Huang, Hengbo; Tang, Rui; Esakky, Prabagaran; Strahle, Jennifer
Abstract : INTRODUCTION: Cerebrospinal fluid (CSF) is essential for the healthy development and function of the brain, but understanding the mechanisms of its distribution in and around the central nervous system (CNS) remains a major challenge. To address this need, we developed a new technique, gold nanoparticle-enhanced x-ray nanotomography (AuNp-XRM), to achieve micrometer-scale resolution visualization of CSF pathways across the entire brain and spinal cord of rodents with further applications to a model of interventricular hemorrhage/post-hemorrhagic hydrocephalus (IVH/PHH). METHODS: P4 rodents were injected with aCSF or hemoglobin to create the control and IVH conditions. 72 hours later, animals underwent MRIs to determine onset of PHH. Animals were then injected with 1.9 nm and 15 nm gold nanoparticles and imaged using XRM. Following XRM, the brains, spines and meninges were harvested for histology. RESULTS: Using AuNp-XRM, we demonstrate visualization of previously characterized glymphatic, cranial nerve, and choroid plexus-mediated CSF circulation patterns, and present evidence to further identify CSF interactions with the leptomeninges, choroid plexus, and parenchyma of the brain and spinal cord. We also identified an intraparenchymal CSF circulation that targets stem-cell rich and cholinergic neuronal populations. CSF distribution to these areas was mediated by flow of CSF through the paravascular spaces of perforators originating from the large blood vessels of the basal cisterns and was significantly decreased in an animal model of PHH. CONCLUSION: Our findings using AuNp-XRM show that cholinergic cell populations in the brain and spinal cord differentially handle CSF, and that PHH alters CSF distribution to these areas of the brain. These region-specific patterns of CSF distribution may have critical relevance to normal brain development, brain development following PHH, and other neuropathological conditions.